Media genre studies in neolinguistic discourse - Dergach, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2025)
The article substantiates the research-based nature of media genre studies as an integral part of the neolinguistic paradigm. It posits the thesis regarding the methodological influence of functionalism on its actualization within the professional interpretation of the literary language resource. The object-oriented approach of contemporary linguistic science presupposes the involvement of not only linguistic criteria and methods but also ideas of the humanities’ various fields. According to the nature of social communication, it includes socio-, psycho-, and cognitive linguistics, philosophy, logic, ethics, aesthetics, etc. This, in the author’s view, makes it possible to identify an intellectualized sequence and continuity of professional observations which, considering the inherent novelty of science, adapt to objective reality. Consequently, an established research tradition continues to evolve through an active stylistic search into the nature and functions of language units within formalized contexts delineated by genre constants. The article also outlines new approaches to the description and analysis of communicative constructions within the architectonics of both traditional and new media genres, thereby contributing to the dynamism of contemporary scholarly thought. The field of mass media is defined as an optimal source for analyzing the development of its formal, genre, functional and stylistic dominants. It is proposed to view media genres not from a linear and descriptive perspective focused solely on their generalized linguistic features, but rather within the context of the functional and stylistic dynamics of the mass information sphere. The author pays attention to the fact that the locus of media genre studies is marked by its topicality and relates to innovative formulations concerning ideas and prospects for genre analysis projected onto media stylistics. It constitutes the subject matter of media genre studies. The object of analysis of this new field, along with its purpose, tasks, originality, and research potential, is also defined, ultimately resulting in the identification of development trends in contemporary society that are intrinsically linked to language communication.